Urgency Religious Moderation in Creating an Attitude of Community Tolerance in Hamlet XV Pematang Johar Village - Disti Adila Sani; Cahya Khairani; Lita Octaviani; Risa Fadila; Habib Lauda Nararya; Agustini; Cut Nalda Sari (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
Not only experiencing differences in religion, but the residents of Pematang Johar Village also consist of various ethnicities. Starting from Malay, Batak, Javanese, Banjar, Banten and others. Therefore, religious moderation and tolerance are very important things to be prioritized in religious life. Religious moderation is very important because tolerance in religious moderation is a good way to deal with threats in religious life. This research uses descriptive qualitative research. The descriptive qualitative method adjusts the opinion between the researcher and the informant. The people of Pematang Johar Village, even though they have different religions, still help each other if there are activities. Mutual respect and appreciation when it comes to worship are also good enough. Then, when there is an invitation for Muslims, they do not hesitate to help financially and in terms of energy. We are born with many differences, including different ethnicities, religions, and races, but all of this is not our will but has become the destiny of the almighty. Every difference should not be used as a mistake in socializing and socializing.